Immunity of State Owned Non-Commercial Ships and Vessel Protection Detachments in the Foreign Criminal Jurisdiction - Nikhilesh, Nikhilesh (Hasanuddin Law Review, 2020)
This article studying the issue of sovereign immunity of ships and vessel protection detachments from criminal jurisdiction of foreign courts. The issue immunity of ships from foreign criminal jurisdiction can be understand from Schooner Exchange case onwards. In the initial stages the courts were given absolute immunity of the government ships in the foreign jurisdiction. Later on the courts, jurists and states classified the immunity in two heads such as personal immunity and functional immunity. Immunity not only given to the troika but also to the other officials engaged in the sovereign functions for their respective states with the exception of universal crimes. The status of the warships, government non commercial ships under the law of the sea convention is analysing.Â Â At the end the Article considering whether functional immunity applicable to the vessel protection detachments appointed by the states to protect their ship from piracy in accordance with the IMO guidelines.